Hubungan Faktor Individual, Sosial dan Pekerjaan dengan Kepuasan Kerja Perawat di Instalasi Gawat Darurat RSUP Dr. M. Djamil Padang Tahun 2013 : The Relationship between Individual, Social and Occupational Factors and Job Satisfaction of Nurses in the Emergency Department of Dr. M. Djamil Padang Hospital in 2013 - Rusmanwadi; Yulastri Arif; Ema Julita (NERS Jurnal Keperawatan, 2013)
Employee dissatisfaction in the work will have an unfavorable situation for the organization and individual. Indicator of job dissatisfaction seen in ER DR M Djamil Hospital is the high rate of absenteeism, increased morbidity, turn over and the other of work discipline problems. This study purposes to determine the relationship of individual factors (interests and attitudes), social factors (interactions with fellow nurse and supervisor) and occupational factors (work conditions and supervision) with job satisfaction of nurses in emergency rooms DR M Djamil Hospital Padang. Research design using descriptive analytic with cross sectional study in which the sample is the entire population and nurses in emergency rooms DR M Djamil Hospital Padang, amounting to 45 people. To determining of the relationship between variables using chi square test and logistic regression. The test results are statistically significant relationship between interests and job satisfaction (p=0.004), attitudes and job satisfaction (p=0.003), the interaction of employees with employer and job satisfaction (p=0.000), supervision and job satisfaction (p=0.000), there is no significant relationship between the interaction of fellow employees with job satisfaction (p=0.334), working conditions and job satisfaction (p=0.727),while the results of logistic regression showed that supervision is the most dominant variables associated with job satisfaction (p=0.002) Expected results of the study can be used by managerial of nursing to further improve the job satisfaction of nurses in order to improve the quality of health services, especially nursing care in the ER.